Analysis of governance and behavior of the population facing the dissemination of COVID-19 in three municipalities in the state of Tocantins, Brazil (Research, Society and Development, 2022)
The objective of this study was to analyze the control strategies of the pandemic caused by COVID-19 from the comparison of normative acts, population structure, movement, and managers' discourse in three municipalities in the state of Tocantins, Brazil, namely, Araguaína, Gurupi, and Palmas. The objective was to understand the dynamics of the spread of the virus occurring in the year 2020. The research was conducted in the period from March 11 to December 31, 2020. The data were systematized in the categories analysis of normative acts, characterization of the structure of the population and managers' speech, looking for their relations with the rate of occurrence registration and death by COVID-19 in the first year of the pandemic in the municipalities. Data were entered into Microsoft Excel® spreadsheets and analyzed using R Studio software. The three municipalities presented similarities regarding socioeconomic and health indicators. The incidence and prevalence of COVID-19 in the city of Araguaína was intense, with more abrupt growth than in the city of Palmas, which, on its turn, managed to delay the increase in the contamination rate. In Gurupi, on the other hand, the situation was well controlled. As for the adoption of containment measures (normative acts), Araguaína was inconsistent in the adoption of restrictive measures. Palmas and Gurupi, on the other hand, adopted more restrictive and incisive measures. The adherence to social distancing, expressed by the IPD, was high. However, right after the first decrees, there was a reduction over time. In Gurupi the mobility was relatively higher, but remained constant throughout the period.